2020
DOI: 10.1021/acsaem.0c01118
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Na-Ion Storage Mechanism in Na3+xV2–xMx(PO4)3 (M = Ni2+, Co2+, Mg2+; x = 0.1–0.5) Cathodes

Abstract: Bivalent cations (M = Ni 2+ , Co 2+ , Mg 2+ ) with different doping contents (x = 0.1, 0.2, 0.3, 0.4, 0.5) were incorporated for vanadium in the Na 3+x V 2−x M x (PO 4 ) 3 (NVP), yielding enhanced rate performance and capacity retention. Successful doping of these cations in the NVP structure was confirmed by powder X-ray diffraction (PXRD), vibrational FT-IR spectroscopy, and scanning electron microscopy (SEM) techniques. The improved electrochemical performance of substituted NVP cathode has been correlated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 60 publications
1
17
0
Order By: Relevance
“…Upon subsequent sodiation/desodiation, ≈2.18 Na + reversibly inserted into and extracted from the VMF-0.5 framework. Such a reversible structure evolution involved in both solid-solution and biphase electrochemical reactions has also been demonstrated in other similar NASICON cathodes, such as typical Na 2 VTi(PO 4 ) 3 , [10] Na 3 TiMn(PO 4 ) 3 , [22] Na 4 VMn(PO 4 ) 3 , [23] Na 3 VFe(PO 4 ) 3 , [23] Na 3 V 2 (PO 4 ) 3 , [34] Na 3 VCr(PO 4 ) 3 , [59,60] etc. The total unit volume variation (Figure S21, Supporting Information) during Na + insertion and extraction processes was calculated as 8.41% (ΔV/V pristine ), which is close to that of NVP cathode (8.26%) [61] and smaller than that of VM reported (9.28%).…”
Section: Resultssupporting
confidence: 69%
“…Upon subsequent sodiation/desodiation, ≈2.18 Na + reversibly inserted into and extracted from the VMF-0.5 framework. Such a reversible structure evolution involved in both solid-solution and biphase electrochemical reactions has also been demonstrated in other similar NASICON cathodes, such as typical Na 2 VTi(PO 4 ) 3 , [10] Na 3 TiMn(PO 4 ) 3 , [22] Na 4 VMn(PO 4 ) 3 , [23] Na 3 VFe(PO 4 ) 3 , [23] Na 3 V 2 (PO 4 ) 3 , [34] Na 3 VCr(PO 4 ) 3 , [59,60] etc. The total unit volume variation (Figure S21, Supporting Information) during Na + insertion and extraction processes was calculated as 8.41% (ΔV/V pristine ), which is close to that of NVP cathode (8.26%) [61] and smaller than that of VM reported (9.28%).…”
Section: Resultssupporting
confidence: 69%
“…In this technique, during charging and discharging a constant current pulse is applied for fixed time period, which is shown in the Figure 10(a). The Na + diffusion coefficient (D Na+ ) of Na 3.94 V 0.98 Mo 0.02 Mn(PO 4 ) 3 @C cathode is calculated by using Weppner and Huggins derived expression as shown below: [32] DNa+=4L2πτΔnormalEs4ptΔEnormalt2 $\vcenter{\openup.5em\halign{$\displaystyle{#}$\cr D{_{{\rm Na}+}}={{{{4\hskip0.17em\hskip0.17em{\rm L}}^{2}{\rm \ }}\over{{\rm \pi }{\rm \tau }}}\left[{{{\Delta {\rm E}}_{{\rm s}}{\rm \ }}\over{{\Delta {\rm E}}_{{\rm t}}}}\right]}^{2}\hfill\cr}}$ …”
Section: Resultsmentioning
confidence: 99%
“…In this technique, during charging and discharging a constant current pulse is applied for fixed time period, which is shown in the Figure 10(a). The Na + diffusion coefficient (D Na + ) of Na 3.94 V 0.98 Mo 0.02 Mn(PO 4 ) 3 @C cathode is calculated by using Weppner and Huggins derived expression as shown below: [32]…”
Section: Chemphyschemmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, various cation-doped Na 3 V 2– x M x (PO 4 ) 3 (M: Al 3+ , Ni 2+ , Mg 2+ , Mn 2+ , Cr 3+ , Nb 5+ , Mo 6+ , etc.) have been developed by partially replacing V 3+ ions, realizing remarkably enhanced electrochemical performance. Masquelier et al reported the substitution of V sites by Al, which can not only facilitate the ion conductivity but also partially activate 3rd Na + extraction/insertion, realizing higher specific capacity and energy density .…”
Section: Introductionmentioning
confidence: 99%